RECONSTRUCTION OF INDONESIAN AGREEMENT LAW - Miftah Arifin (Jurnal Pembaharuan Hukum, 2015)
In line with the development of a society that increasingly has been complex in modern times, there grow a variety of risks which are potential to be threats to any parties who haveexpectations for the success of the transactions they conduct. To realize the expectations, there has been developed the norms of law in the form of a set of principles and the rule of law. They are commonly understood as a legal contract or legal agreement (law of contracts) that is expected to increase certainty, justice and predictability and at the same time a device for parties to manage risk (risk management device).The development of treaty law set out in Book III of the Civil Code is affected by legislation such as the Basic Agrarian Law and Consumer Protection Law, judicial decisions and practicescarried out by the parties in their dealings. Basic Agrarian Law and its implementation rules give legal certainty to buyers with good intention.That’s why the future of the Indonesian National Contract Law should be developed by adhering to some of the main qualities, namely: first, it must be derived from the values of Pancasila and the Preamble and the relevant provisions of the Act of 1945. In other words, thoughts rising from the philosophy of life of the Indonesian nation and the constitutional basis of the Republic of Indonesia must become a national political treaty law; legal and political as far as possible is what animates the substance of Law of the National Agreement; second, must be designed as a sub-codification of law codification National Commitments to come, so that the preparation of the Law on National Contract Law would be prepared in anticipation of the general principles of the new Indonesian Engagements law; third, it must be designed as the foundation for the Law of Treaties of Indonesia, without having to assign a specific orientation to the civil law, common law, Islamic law or customary law, or other legal traditions. Law onNational Contract Law should be developed as a typical Indonesian Contract Law, because it is in line with the principles of Pancasila values. Yet, it should be able to answer legal issues.